An improvement on the technique of transosseous tunnels for the fixation of lower pole patella fracture: Cerclage around the patella. Issue 9 (4th March 2022) - Hu, Jialang; Guo, Xin
Abstract : Abstract: The technique of transosseous tunnels is widely used in lower pole patella fracture (LPP). Though the extensor mechanism can be restored, distal avulsion fragments are usually unstable. The subsequent fracture gap and nonunion impair the extensor mechanism in turn. Cerclage is a promising method for treating the condition. The aim of this prospective cohort study is to determine if cerclage around the patella combined with the technique of transosseous tunnels stabilizes the avulsion fragments and brings out improved outcomes on LPP. Twenty two patients with LPP were treated with the hybrid technique. The patients were followed up and evaluated clinically and radiographically. The functional outcome was assessed by the average range of knee movement and Lysholm knee rating system at 6 months after surgery, as well as the final follow-up. Radiologically, Insall-Salvati ratio and the time from surgery to bone union were assessed. Postoperatively, with a mean followed-up of 12 months. All of the patients regained stability of the knee with an average range of movements of 131.8 degrees at 6 months after operation and 138.2 degrees at the final follow-up. On the Lysholm knee rating system, all cases were classified as excellent. The average score was 93.2 at 6 months after operation and 95.9 at the final follow-up. In radiological assessment, no fracture gap or nonunion occurred. The average Insall-Salvati ratio (I-S ratio) was 1.03. The hybrid technique offers further stabilization for the avulsion fragments and strengthens attachment of the patellar tendon, which brings forward time of rehabilitation and achieves good clinical outcomes.